Clock Difference Diagrams - Larsen, Kim G.; Weise, Carsten; Yi, Wang; Pearson, Justin (BRICS Report Series, 1998)
We sketch a BDD-like structure for representing unions of simple convex polyhedra, describing the legal values of a set of clocks given bounds on the values of clocks and clock dffierences.